2023
DOI: 10.3389/fendo.2023.1126339
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the association between genetic factors regulating thyroid function and microvascular complications in diabetes: A two-sample Mendelian randomization study in the European population

Abstract: BackgroundObservational studies have identified a possible link between thyroid function and diabetic microangiopathy, specifically in diabetic kidney disease (DKD) and diabetic retinopathy (DR). However, it is unclear whether this association reflects a causal relationship.ObjectiveTo assess the potential direct effect of thyroid characteristics on DKD and DR based on Mendelian randomization (MR).MethodsWe conducted an MR study using genetic variants as an instrument associated with thyroid function to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Another MR study reported that type 2 diabetes and kidney disease increased plasma levels of the GM-dependent metabolite trimethylamine oxide (TMAO) and proposed that the earlier observational evidence of elevated risk of cardiovascular diseases with higher TMAO levels might have been the result of confounding or reverse causality rather than a causal effect [54]. Another recent study suggested that certain bacterial genera could have a causal link to type 2 diabetes [55]. Considering the limitations of both MR (e.g.…”
Section: Role Of Mr In Elucidating Causal Effectsmentioning
confidence: 99%
“…Another MR study reported that type 2 diabetes and kidney disease increased plasma levels of the GM-dependent metabolite trimethylamine oxide (TMAO) and proposed that the earlier observational evidence of elevated risk of cardiovascular diseases with higher TMAO levels might have been the result of confounding or reverse causality rather than a causal effect [54]. Another recent study suggested that certain bacterial genera could have a causal link to type 2 diabetes [55]. Considering the limitations of both MR (e.g.…”
Section: Role Of Mr In Elucidating Causal Effectsmentioning
confidence: 99%
“…Substrate mapping, involving identifying scar tissue and abnormal electrograms, plays a crucial role in VT ablation [35]. Stereotactic body radiation therapy (SBRT) has emerged as a novel non-invasive approach for refractory VT [36]. SVTs, including atrioventricular nodal reentrant tachycardia (AVNRT) and atrioventricular reentrant tachycardia (AVRT), are amenable to catheter ablation.…”
Section: Innovations In Arrhythmia Managementmentioning
confidence: 99%
“…Patients can now access their medical records, schedule appointments, and receive real-time health data, empowering them to participate in their care actively [36]. Advances in genomics and precision medicine have allowed for tailored treatment plans based on an individual's genetic makeup.…”
Section: Advancements In Patient-centered Carementioning
confidence: 99%